Can monocyte to HDL ratio be used as an inflammatory marker in children with familial mediterranean fever? - Gunes, Hatice; Duksal, Fatma; Parlak, Mesut (Annals of Medical Research, 2021)
Aim: Familial Mediterranean fever (FMF); is an auto-inflammatory disease characterized by recurrent fever attacks. Inflammation continues even in the attack-free period. Monocyte to high-density lipoprotein cholesterol (HDL-C) ratio (MHR) is an inflammatory marker that has recently begun to use. The aim of the study was to evaluate the relationship between MHR and FMF in children.Material and Methods: Sixty-two children with FMF in the attack-free period and 60-age and sex-matched- healthy controls included in the study. Patients divided into subgroups according to their gene mutation type. Monocyte count and HDL-C levels retrieved from medical records of patients and MHR were calculated from these data. Results: The MHR of individuals were close to each other and there was no statistically significant difference between them ( p>0.05). Twenty-four of the patients had heterozygous, 4 had homozygous, 11 had a compound and 21 had negative mutations. Two of the patients had no mutation analysis. There was no significant difference between these four groups according to MHR (p=0.348). However, MHR revealed a positive correlation with fibrinogen (r=0.604, p0.005, n=24), serum amyloid A (r=0.437, p=0.005, n=39), C-reactive protein (r=0.277, p=0.005, n=101), and erythrocyte sedimentation rate (r=0.404, p0.001, n=104).Conclusion: As a result, we showed MHR was not different from healthy controls in FMF patients. Contrary to what is claimed, the use of MHR as an inflammatory marker in FMF is doubtful.Keywords: Monocyte hdl ratio; familial mediterranean fever; inflammation marker.
Keywords: Monocyte hdl ratio; familial mediterranean fever; inflammation marker.